2003
DOI: 10.1016/s1044-0305(02)00807-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cu(II) in matrix-assisted laser desorption/ionization mass spectrometry

Abstract: The mechanisms of the reduction of Cu(II) in matrix-assisted laser desorption/ionization mass spectrometry (MALDI) are studied. In MALDI mass spectra, ions cationized by copper mostly contain Cu(I) even if Cu(II) salts are added to the sample. It was found that Cu(II) was reduced to Cu(I) by gas-phase charge exchange with matrix molecules, which is a thermodynamically favorable process. Under some conditions, large amounts of free electrons are present in the plume. Cu(II) can be even more efficiently reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 41 publications
4
72
1
Order By: Relevance
“…In the ion source, gas-phase reactions, such as redox reactions, may occur between the electronically excited analyte ions and matrix ions/molecules. For example, the mechanism of the reduction of Cu (II) to Cu (I) in MALDI was studied, and it was found that this reduction was caused by gas-phase charge exchange with matrix molecules, which is a thermodynamically favorable process [15]. Recently, studies of a MALDI insource photo-oxidation reaction have shown that on a photoelectrode-modified target plate, hydroquinone can be photo-oxidized to benzoquinone by UV laser excitation [16].…”
mentioning
confidence: 99%
“…In the ion source, gas-phase reactions, such as redox reactions, may occur between the electronically excited analyte ions and matrix ions/molecules. For example, the mechanism of the reduction of Cu (II) to Cu (I) in MALDI was studied, and it was found that this reduction was caused by gas-phase charge exchange with matrix molecules, which is a thermodynamically favorable process [15]. Recently, studies of a MALDI insource photo-oxidation reaction have shown that on a photoelectrode-modified target plate, hydroquinone can be photo-oxidized to benzoquinone by UV laser excitation [16].…”
mentioning
confidence: 99%
“…The latter processes may be responsible for oxygen release, effectively stabilizing the resulting species. The occurrence of these mechanisms has been recently demonstrated for copper chlorides and small peptides deposited on different conductive and isolating surfaces [63][64][65]. Moreover, these electrons may also ionize neutrals species if their kinetic energy is high enough [21].…”
Section: Study Of Cluster Ion Formation By La-msmentioning
confidence: 97%
“…34 Furthermore, Cu(II) ion reduction was inversely proportional to the concentration of the analytes, and thus the thickness of the deposited analyte would affect the reduction, as in the case of MALDI. 16,25 These findings suggest that electron transfer from the sample target to analytes is likely in DIOS as well, although the ionization mechanism of DIOS is unknown.Juhasz and Costello reported on the oxidation of oligomers and polymers containing ferrocene and ruthenocene moieties in MALDI measurements. 37 They described that either electron transfer from the analyte to the chemical matrix or direct photoionization of the analayte could account for their results.…”
mentioning
confidence: 99%
“…34 Furthermore, Cu(II) ion reduction was inversely proportional to the concentration of the analytes, and thus the thickness of the deposited analyte would affect the reduction, as in the case of MALDI. 16,25 These findings suggest that electron transfer from the sample target to analytes is likely in DIOS as well, although the ionization mechanism of DIOS is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation